Local Economic Development and Its Impact on the Tourist Attraction of Pagubugan in Melung Village, Banyumas: Pengembangan Ekonomi Lokal terhadap Daya Tarik Wisata Pagubugan di Desa Melung, Banyumas - Muhammad Tsani , Muhammad Tsani; Ananda, Priska; Mukaromah, Inna Af’idatul; Zulfa, Muhamad Abdan; Fitriani, Sirfi Nur; Maghfiroh, Siti (PADAIDI: Journal of Tourism Dedication, 2024)
The development of community-based tourism in Pagubugan Village, Melung, Banyumas, aims to leverage local potential to enhance rural economic growth. However, the tourism sector faces significant challenges, including a lack of innovation, insufficient human resources (HR) capacity, and limited access to funding. These challenges have hindered the village's ability to sustain its tourism activities and attract visitors. This study aims to analyze the impacts of these challenges on the degradation of tourism in Pagubugan and to propose strategic solutions for revitalization. A qualitative research approach was employed, utilizing Miles and Huberman's data analysis method, which includes data reduction, data presentation, and conclusion drawing. Data were collected through in-depth interviews with local stakeholders, field observations, and document analysis to identify the core issues affecting tourism development. The findings highlight that limited innovation in tourism management, a lack of trained HR, and constrained financial resources have led to stagnation in tourism growth. Tourism programs and infrastructure projects have been delayed or abandoned due to funding shortages, while insufficient HR training has resulted in low service quality and poor competitiveness. Furthermore, inadequate promotion through digital platforms has restricted the village's visibility in broader markets.